1.7 to 2.3 Gbps OOK LED VLC Transmission Based on 4 × 4 Color-Polarization-Multiplexing at Extremely Low Illumination - Chien-Hung Yeh; Jui-Hung Weng; Chi-Wai Chow; Chien-Ming Luo; Yue-Ru Xie; Chien-Ju Chen; Meng-Chyi Wu (IEEE Photonics Journal)
To achieve the high traffic rate of a GaN LED-based visible light communication (VLC), a 4 × 4 color-polarization-multiplexing system is demonstrated by using two blue and two green LEDs. In the measurement, an available bandwidth of blue and green LEDs can be greater than 465 MHz for VLC modulation traffic by using the suitable analogy front end circuit. Hence, the proposed VLC system can deliver 1.7 to 2.3 Gbit/s on–off keying traffic rates in the free space transmission length of 1–4 m under the extremely low illumination of 6.9–136.1 lux for the indoor application. Moreover, the measured BER of each LED is less than the forward error correction target of 3.8 × 10−3 to maintain the better signal performance.